2018
DOI: 10.1016/j.apsusc.2018.01.087
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion induced atomic islands on the surface of Ni/Cu nanolayers

Abstract: Surface islands formed by grain-boundary diffusion has been studied in Ni/Cu nanolayers by in-situ low energy ion scattering spectroscopy, X-ray photoelectron spectroscopy, scanning probe microscopy and ex-situ depth profiling based on ion sputtering.In this paper a new experimental approach of measurement of grain-boundary diffusion coefficients is presented. Appearing time of copper atoms diffused through a few nanometer thick nickel layer has been detected by low energy ion scattering spectroscopy with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The atomic flux through the copper layer continuously decreased with time and finally halted. This saturation effect of surface coverage was also experienced previously in Ni/Cu bilayer systems by Cu diffusion through a Ni layer [ 12 ], suggesting that this is a general effect in thin layers.
Fig.
…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The atomic flux through the copper layer continuously decreased with time and finally halted. This saturation effect of surface coverage was also experienced previously in Ni/Cu bilayer systems by Cu diffusion through a Ni layer [ 12 ], suggesting that this is a general effect in thin layers.
Fig.
…”
Section: Resultssupporting
confidence: 77%
“…LEIS is a surface sensitive method that enables the composition analysis of the few top-most surface atomic layers. Study of atomic diffusion by LEIS was first achieved by the authors of the paper [ 12 ]. In the present experiments, a helium ion beam of 1 keV/10 nA was used to scan sample surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…It can be observed that titanium was deposited from the surface to the sample, but the expected Tin was not formed near the edges because in this point the iron content was higher than in the middle; moreover, the nitrogen content was decreased too. XPs analysis was performed for a more accurate determination [19,20] which results are seen in Table 6.…”
Section: Plasma Nitriding Of Tempered Steel With Titanium Active Screenmentioning
confidence: 99%